2014
DOI: 10.1016/j.ypmed.2014.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Using appropriate body mass index cut points for overweight and obesity among Asian Americans

Abstract: Objective Asian Americans have low prevalence of overweight/obesity based on standard BMI cut points yet have higher rates of diabetes. We examined the prevalence of overweight/obesity, using lower BMI cut points recommended by the World Health Organization (WHO) for Asians, and diabetes in Asian American subgroups in California. Method Secondary analysis of the 2009 adult California Health Interview Survey (n = 45,946) of non-Hispanic Whites (NHW), African Americans, Hispanics and Asians (Vietnamese, Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
182
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(193 citation statements)
references
References 43 publications
7
182
3
1
Order By: Relevance
“…In the NHANES data for 2011-2012, the prevalence of obesity was 10.8% among Asian-Americans, 32.6% among non-Hispanic whites, 42.5% among Hispanics, and 47.8% among non-Hispanic blacks (Ogden et al, 2014). Some of this difference is due to the fact that BMI ignores differences in body composition, and as a result BMI understates obesity in Asian-Americans (Jih et al, 2014) and overstates it in African-Americans (Burkhauser and Cawley, 2008). Within most race/ethnic groups, the prevalence of obesity is similar for women and men, but this is not true for African-Americans, among whom the prevalence of obesity is much higher among women (56.6%) than men (37.1%) (Ogden et al, 2014).…”
Section: Explaining Disparities and Heterogeneity In Effectsmentioning
confidence: 99%
“…In the NHANES data for 2011-2012, the prevalence of obesity was 10.8% among Asian-Americans, 32.6% among non-Hispanic whites, 42.5% among Hispanics, and 47.8% among non-Hispanic blacks (Ogden et al, 2014). Some of this difference is due to the fact that BMI ignores differences in body composition, and as a result BMI understates obesity in Asian-Americans (Jih et al, 2014) and overstates it in African-Americans (Burkhauser and Cawley, 2008). Within most race/ethnic groups, the prevalence of obesity is similar for women and men, but this is not true for African-Americans, among whom the prevalence of obesity is much higher among women (56.6%) than men (37.1%) (Ogden et al, 2014).…”
Section: Explaining Disparities and Heterogeneity In Effectsmentioning
confidence: 99%
“…1,2 Weight gain after migration is common as well, 3,4 but the increase in diabetes occurs despite a generally low prevalence of overweight and obesity in this population. 1,2,5 The rapid change in risk upon migration suggests a role for acculturation-related lifestyle factors. Studies conducted among Asian immigrants to the United States, Canada, and Australia suggest poorer metabolic profiles with longer residence in adoptive countries, [6][7][8] but the Multi-Ethnic Study of Atherosclerosis (MESA) showed no association between acculturation and diabetes among its Chinese participants.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus was defined as the fasting blood sugar level ≥ 100 mg/dL (International Diabetic Federation criteria) (10) , Dyslipidemia with serum high-density lipoprotein (HDL) level < 40 mg/dL, and triglyceride levels > 150 mg/dL (International diabetic Federation criteria).Body mass index (BMI)was calculated for all the patients by recording their weight and height. Obesity was defined as BMI> 30 kg/m 2 , according to WHO criteria (11) . Patients underwent a brain MRI by following the standard procedure using 1.5-Tesla MRI system (Siemens Magnetom Symphony, Siemens Medical Solutions, USA Inc., Malvern, Pennsylvania).…”
Section: Methodsmentioning
confidence: 99%